2009
DOI: 10.1016/j.otsr.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Results of latissimus dorsi tendon transfer for irreparable cuff tears

Abstract: Rupture of the supraspinatus and infraspinatus tendon (and teres minor) can cause loss of active external rotation (ER), entailing severe functional disability in daily activities. Latissimus dorsi tendon transfer (LDTT), proposed by Gerber in 1988, appears to be the best adapted solution in these cases of irreparable posterior and superior cuff tears. Between 2001 and 2004, 30 patients were operated on by the technique described by Gerber, with the transfer fixed anteriorly to the subscapularis tendon and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 28 publications
0
66
0
10
Order By: Relevance
“…With internal rotation, 9 of 14 treated patients showed slightly improved positioning of the humeral head in relation to the glenoid. 37,49 Conclusions This study indicates that, in cases of massive RCT with no subscapularis tear, long-term results of partial repair of the posterior cuff with covering of the infraspinatus footprint showed improved outcome scores. In addition, AHD increased minimally and was stable at final followup.…”
Section: Discussionmentioning
confidence: 66%
“…With internal rotation, 9 of 14 treated patients showed slightly improved positioning of the humeral head in relation to the glenoid. 37,49 Conclusions This study indicates that, in cases of massive RCT with no subscapularis tear, long-term results of partial repair of the posterior cuff with covering of the infraspinatus footprint showed improved outcome scores. In addition, AHD increased minimally and was stable at final followup.…”
Section: Discussionmentioning
confidence: 66%
“…Novè-Josserand [21] reported that of 30 patients treated, all presented recovery of external rotation and disappearance of the hornblower sign, 8% of the patients were still unable to use the operated limb to eat and drink, compared with 64.7% before surgery. Zafra [22] treated 8 patients with this technique and reported pain relief and improved mobility in external rotation in 88.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there appeared to be a correlation between the modified classification of Walch et al and the Constant-Murley score [6] in 200 patients aged 70 to 101 years [21]. This modified classification has been used for selecting candidates for latissimus dorsi transfer [20].…”
Section: Introductionmentioning
confidence: 99%